Constituents of global mindset intensity: empirical evidence from a study of Japanese managers - Ananthram, Subra; Grainger, Richard; Tominaga, H. (Society for Global Business & Economic Development (SGBED), 2011)
During the Meiji Era and again in the aftermath of the Pacific War, Japan rapidly established itself on the world stage as a major participant in global business from very adverse and inauspicious beginnings. In the case of the Meiji Era expansion, the dramatic advances have commonly been interpreted as resulting from the herculean efforts of ex-samurai leaders acting as agents of the administration, and in the post war reconstruction period, a larger societal sub-group, Japanese ‘salary men’. With this background in mind, and coming after a period of some two decades of economic decline, the current empirical research study was undertaken for the purpose of establishing an appropriate mindset ‘profile’ for the contemporary global business era. After establishing the constructs by which ‘global mindset intensity’ could be assessed, a questionnaire survey was undertaken with Japanese international managers in western Japan. Based on their findings, the researchers have tentatively suggested that the ideal corporate role model of Japan’s post war reconstruction and growth period, the ‘salary man’, was now effectively redundant, and that the currently accepted ideal profile was more worldly and individualistic, with expertise and ‘global mindset intensity’ drawn from personalized international business experience, reminiscent of established Western business ideals.